Comprensión lectora en estudiantes (sexto grado - primaria) según género en una institución educativa del distrito de Ventanilla - Ortega Murga, Óscar Jesús (2010)
The research aimed to determine and compare the levels of reading comprehension regarding gender. The sample consisted of 40 sixth grade elementary students from a public school in Ventanilla District. The test of reading comprehension ACL 6º (Catalá et. al. 2001) adapted (Ortega and Ramirez, 2009) was applied. The results showed that 52.6 % of the girls and 66.7% of the boys reached a low level while 42.1 % of the girls and 23.8 % of the boys reached the average level. The high level was only reached by 5.3 % of the girls and 9.5 % of the boys. The data show the low academic performance in reading comprehension in the evaluated students. It also shows there were not are significant relationship in levels of reading comprehension regarding gender.